Result of Digital Marketing, Product Quality and Mediation Customer Satisfaction - Buyung Romadhoni Romadhoni; Akhmad Akhmad; Muhammad Rusydi Rusydi; Mustaking Mustaking (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to analyze and explain the result of 1) customer satisfaction over digital marketing; 2) customer satisfaction over product quality; 3) purchasing decisions over digital marketing; 4) purchasing decision over product quality; 5) customer satisfaction with purchasing decisions; 6) digital marketing on purchasing decisions through customer satisfaction; 7) purchasing decisions on product quality through customer satisfaction. A type approach used in this study is a quantitative approach method. The targeted people in this study are Makassar citizenship which has accounts and users of Shopee services. This study used purposive sampling with a type of judgment sampling is 95 samples. The data is collected by distributing questionnaires to students of Office Automation Management. This study uses the Structural Equational Modeling Partial Least Square (SEM-PLS) analysis method. The study result found: 1) a significant result in customer satisfaction over digital marketing; 2) a significant result in customer satisfaction over product quality; 3) a significant result in purchasing decisions over digital marketing; 4) a significant result in purchasing decision over product quality; 5) a significant result on purchasing decisions customer satisfaction; 6) through customer satisfaction, digital marketing has a significant impact on purchasing decisions; 7) customer satisfaction has a significant impact on purchasing decisions due to product quality.